PENGARUH INTERAKSI ANTARA DUA KOMPONEN FLUIDA DALAM FORMASI GALAKSI TERHADAP FLUKTUASI KERAPATAN - , MONICA NOVIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dynamics of the universe from radiation-dominated to matter dominated has been discussed. Interaction between two fluid components which contain plasma and radiation for galaxy formation and its influence to unstable density fluctuations in the universe has been investigated. The method for investigating this interaction is dispersion-relation method.